Investigation of Mode I fracture toughness of red Verona marble after thermal treatment (Fracture and Structural Integrity, 2015)
The present paper aims to assess the effect of freeze/thaw cycles on fracture behaviour of a naturalstone: the red Verona marble. A wide variety of specimen types and methods to determine Mode I fracturetoughness of natural stones are available in the literature and, in this context, the model originally proposed forplain concrete, i.e. the Two-Parameter Model (TPM), is adopted. Such a method is able to take into account theslow nonlinear crack growth occurring before the peak load, typical of quasi-brittle materials, with the advantageof easy specimen preparation and simple test configuration.In the present paper, the atmospheric ageing is simulated by means of thermal pre-treatments consisting offreeze/thaw cycles. Experimental tests are carried out using three-point bending Single-Edge Notched (SEN)specimens, according to the TPM procedure. The effects of thermal treatment on both mechanical and fractureparameters are examined in terms of elastic modulus and fracture toughness, respectively.KEYWORDS. Mode I Fracture Toughness; Red Verona Marble; Thermal Treatment; Two-Parameter Model.
Keywords: Mode I Fracture Toughness